Six distributional effects of environmental policy - Don Fullerton (Center for Economic Studies and ifo Institute (CESifo), 2010)
While prior literature has identified various effects of environmental policy, this note uses the example of a proposed carbon permit system to illustrate and discuss six different types of distributional effects: (1) higher prices of carbon-intensive products, (2) changes in relative returns to factors like labor, capital, and resources, (3) allocation of scarcity rents from a restricted number of permits, (4) distribution of the benefits from improvements in environmental quality, (5) temporary effects during the transition, and (6) capitalization of all those effects into prices of land, corporate stock, or house values. The note also discusses whether all six effects could be regressive, that is, whether carbon policy could place disproportionate burden on the poor.
Keywords: H23; Q52; 330; tax incidence; climate policy; capitalization effects; general equilibrium; Ökosteuer; Steuerinzidenz; Steuerbelastung; Allgemeines Gleichgewicht; Theorie